Differences The Incidence of Hyperuricemia in Families with Gouty Arthritis and Families Without Gouty Arthritis in Buleleng Regional General Hospital, Bali, Indonesian - Larasati A.Wahyu; Pramarta Y. Dwiputra (Publikasi Indonesia, 2024)
The most common manifestation of hyperuricemia is gout. Hyperuricemia is the leading cause of gout. It is about five times more common than gout. The heritability of hyperuricemia and gout is about 73%, and 40-50% of patients have a family history of gout. Indonesia, especially Bali, has a high prevalence of hyperuricemia in families with gout at 26.6%. Therefore, we performed this study to look for differences in the incidence of hyperuricemia in families with gouty arthritis and families without gouty arthritis. In an unpaired case-control study, which is the target population is Balinese, the target population is Balinese individuals with gouty arthritis who come to the Internal Medicine Polyclinic of Buleleng Regional General Hospital. The controls in this study were Balinese individuals without gouty arthritis; there were 41 samples who made a pedigree and checked serum uric acid at one time. Of the total 41 case-control samples used, the incidence of hyperuricemia in families with gouty arthritis is 65.9%, and in families without gouty arthritis, is 29.3%, with an Odd Ratio (OR) value of 2.25 with a 95% confidence interval, p-value = 0.002. There were differences in hyperuricemia incidence in families with gouty arthritis and families without gouty arthritis with a p-value = 0.002. Hyperuricemia in families with gouty arthritis is 2.25 times (OR) higher than in families without gouty arthritis.